Lung ultrasound scores in neonatal clinical practice: A narrative review of the literature. Issue 5 (28th March 2022) - Corsini, Iuri; Ficial, Benjamim; Ciarcià, Martina; Capasso, Letizia; Migliaro, Fiorella; Rodriguez‐Fanjul, Javier; Clemente, Maria; Raimondi, Francesco; Dani, Carlo
Abstract: Lung ultrasound (LU) has in recent years increasingly been used as a point‐of‐care method. Initially, LU was used as a so‐called descriptive diagnostic method for neonatal respiratory diseases. Instead, this review article focuses on the use of LU as a "functional" tool using classification of findings in patterns or using semiquantitative scores. We review and describe the evidence that led to the implementation of LU in predicting the need for surfactant replacement therapy in preterm infants and in the identification of newborns at risk of developing bronchopulmonary dysplasia. LU appears to be a very promising method for the future of clinical management of newborns in both acute and chronic phases of pulmonary pathologies related to prematurity. However, further studies are needed to define its role before full implementation.